Supervisory influence support and work life balance on employee turnover is mediated by work engagement at Mie Mapan restaurant - Muchammad Choirul Anam; Ayu Lucy Larassaty (Jurnal Mantik, 2024)
This research aims to find out whether there is an influence supervisor support and work life balance on employee turnover mediated by work engagement. The research was conducted on 70 employees of an established noodle restaurant. The analytical method used is quantitative. The results of this study indicate that Supervisor Support has no effect on employee turnover. Supervisor Support has an influence on work engagement. Work life balance does not affect employee turnover. Work life balance has no effect on work engagement. Work engagement influences employee turnover. This means that increasing supervisor support will have an impact on employee turnover which is mediated by work engagement